The effect of in vitro gastrointestinal digestion on the anti-inflammatory activity of Vitis vinifera L. leaves. Issue 8 (5th August 2015) - Sangiovanni, E.; Di Lorenzo, C.; Colombo, E.; Colombo, F.; Fumagalli, M.; Frigerio, G.; Restani, P.; Dell'Agli, M.
<x xml:space="preserve">Abstract</x> Vitis vinifera L. water extract from dried leaves maintains its anti-inflammatory activity after in vitro gastric digestion.